Alternative pre-mRNA splicing and proteome expansion in metazoans. - Maniatis, T.; Tasic, B. (Nature, 2002)
The protein coding sequences of most eukaryotic messenger RNA precursors (pre-mRNAs) are interrupted by non-coding sequences called introns. Pre-mRNA splicing is the process by which introns are removed and the protein coding elements assembled into mature mRNAs. Alternative pre-mRNA splicing selectively joins different protein coding elements to form mRNAs that encode proteins with distinct functions, and is therefore an important source of protein diversity. The elaboration of this mechanism may have had a significant role in the expansion of metazoan proteomes during evolution.